226k views
4 votes
How do you solve f (x)=-3 (x+2)+2

1 Answer

2 votes

Answer:

−1/3y+−4/3

Explanation:

We need to solve for x.

How? Easy! :D

Step one: Flip the equation. (In class we call it the 'flip-flop'.) When you do this, you should have your equation look like this:

−3x−4=y

Step two: Add 4 to both sides of the equation. When you do this step, your problem should look like this:

−3x−4+4=y+4

−3x=y+4

Step three: Divide both sides by -3.

-3x/-3 = y+4/-3.

Step four: Wrap-up. What the answer is.

x = -1/3y + -4/3

Final step: OUR ANSWER!

x = -1/3 + -4/3

Hope this helped! :D

User Mr Alpha
by
6.4k points